Perbaikan Subgrade pada Jalan Kampung Keramat di Kota Pangkalpinang dengan Menggunakan Kapur Padam Sebagai Bahan Stabilisasi Tanah - Ferra Fahriani; Desy Yovianti; Eko Saputra; Merley Misriani (Jurnal Ilmiah Rekayasa Sipil, 2020)
Soil is the main support in a construction. Unstable soil conditions, especially in the subgrade can cause damage to the road. Based on the results of a direct survey in the field, it was found that the condition of the Jalan Kampung Keramat in Pangkalpinang City was damaged. This might be caused by the condition of the subgrade on the road which is unstable and the subgrade is categorised as clay soil type. This study aims to improve the subgrade on Jalan Kampung Keramat in Pangkalpinang City by using limestone as a soil stabilization material. This study used an experimental method in the laboratory by making mixture between clay soil and limestone with four different variations in the percentage of limestone, namely 0%, 3%, 5%, 7%. There are four parameters of the mixed characteristics that are tested and analysed, namely: the Atterberg limit, specific gravity, soil gradation and CBR value. The results show that the Atterberg limit values ​​(liquid limit-LL and plasticity index-IP) and specific gravity tend to decrease with increasing percentage of limestone extinguished. However, the plastic limit value (PL) shows the opposite tendency, i.e. it increases with the decreasing percentage of limestone. The specific gravity values ​​obtained based on the percentage of lime outages (0%, 3%, 5%, 7%) are 2.63, 2.61, 2.60, and 2.58, respectively. In addition, the addition of limestone causes changes in soil gradation, namely the addition of retained fraction # No.200 and the reduction of passed fraction # No.200. The Addition of limestone can increase the CBR value of the soil, where the addition of 7% of limestone produces the highest CBR value (21.3%) compared to 5% limestone (15.7%), 3% limestone (13.4%) and 0% limestone (11.2%). Therefore, using limestone can improve quality of subgrade, which can be seen from the value of CBR obtained.